Peran Dosen dalam Upaya Penguatan Nilai-Nilai Moderasi Beragama Melalui Konsep Islam Wasathiyah - Mayaningsih, Afifah (Revorma: Jurnal Pendidikan dan Pemikiran, 2023)
Religion is a crucial matter that is often divided even though the Indonesian constitution guarantees religious freedom for all. In 2019, the Equal Institute mentioned 23.4% of Indonesian students, up to 10 prominent state colleges exposed to radicalism. Such a fact necessitates a specific strategy to counter the spread of the perception of radicalism. Strengthening these values of religious moderation, becomes one of the main indicators as an effort to build the culture and character of the nation. The world’s scholars also created a new focus on religious life with the Islamic term Wasathiyah. The idea was launched in 2015. Islam Wasathiyah is a new breakthrough in Islamic moderation in Indonesia. Through this wasathiyah concept, lecturers, as agents of change in the higher education environment, have a great responsibility in shaping a student's understanding of religion that is balanced, inclusive, and has a positive impact. Therefore, this article outlines how lecturers can be role models and facilitators in educating students about the Islamic concept of Wasathiyyah, providing examples of practice of moderation in worship, as well as encouraging inclusive interreligious dialogue.